Geometry evolution of mesoscopic mechanical structures during the rock fragmentation process induced by tunnel boring machine (TBM) cutters - Geng, Qi; He, Fei; Lu, Zhiyong; Liu, Xiaohui; Wang, Xuebin; Ye, Min (Royal Society open science, 2022)
We investigated the geometric evolution of mesoscopic mechanical structures in rocks during the rock fragmentation process induced by tunnel boring machine cutters. Numerical models were built using a grain-based discrete element method to accurately represent the mesoscopic structures and macroscopic mechanical behaviours of rocks, and the relationship between the mesoscopic evolution and the macroscopic response of rock was determined. The major results are as follows. First, the crushing and re-compaction of the grains were found to mainly occur in the thin crushed zone immediately beneath the cutter tip. Second, the reduction in the bearing ability of the dense core during cutter indentation was due to the order increment of the contact topological structure at the mesoscopic scale. Third, the area percentages of low- and high-order meso-loops decreased and increased, respectively, during the indentation process, and the volume expansion of the dense core was mainly caused by an increase in the internal pore area of high-order meso-loops that have low internal solid fractions. Fourth, the low-order meso-loops primarily bore and transferred the indentation force. Finally, the distribution contour of the meso-loops was found to be an appropriate and intuitive approach for representing the evolution of cracks on a macroscopic scale.